Effect of supplementing urea molasses blocks in the ration of buffaloes on nutrient utilization and milk production - CHAUHAN, T R; GUPTA, R; DAHIYA, S S; PUNIA, B S (The Indian Journal of Animal Sciences, 2013)
Lactating buffaloes (25) in their mid lactation yielding 7-8 litres of milk were divided into 5 groups of 5 each and were allotted to 5 treatments, viz. control. and treatments T-1, T-2, T-3 and T -4. The buffaloes were of fered wheat straw (W.S) ad lib. + green berseem + 3-4 kg concentrate mixture in control groups, while 20% of the concentrate mixture was replaced by urea molasses mineral block (UMB) containing cottonseed-cake, deoiled mustard-cake, guar-meal and deoiled groundnut-cake as varied degradable protein sources in T-1, T-2, T-3 and T -4 groups respectively. The voluntary DM intake (kg/100 kg BW) was recorded as 2.97.2.95,3.05, 2.05, and 3.04 in the control, T-1, T -2, T -3 and T -4 groups respectively. The curtailment of 20% concentrate mixture in T -1. T -2. T -3 and T -4 groups was well compensated by consuming 670. 653. 673 and 633 g ofUMB respectively. The digestibility of various nutrients. was similar in all the treatment groups. Throughout the experimental period of 84 days. all the lactating buffaloes maintained their body weights. The quality and quantity of milk produced remained unaffected in all the treatments due to the substitution of concentrate mixture with .UMB. It is concluded that by supplementing UMS ad lib. along with wheat straw as basal roughage to the milch buffaloes yielding 7-8 litres of milk. in their mid-lactation. 20% of the concentrate mixture can be saved.